2004
DOI: 10.1038/sj.bmt.1704614
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of targeted itraconazole prophylaxis in patients with graft-versus-host disease at high risk of invasive mould infections following allogeneic stem cell transplantation

Abstract: Summary:Patients with severe graft-versus-host disease (GVHD) requiring intensive immunosuppression are at high risk of invasive mould infections (IMI). Prophylaxis with an active, oral antifungal agents with reliable absorption in this context is desirable. A total of 44 patients at high risk of post-engraftment IMI received itraconazole solution 2.5 mg/kg b.d. as prophylaxis. Two of the first nine patients, in whom bioavailability was compromised due to significant vomiting and/or diarrhoea, died of probable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This risk‐adjusted approach has practical implications for clinicians. Most centres, including those in Australia, report that pre‐engraftment, invasive mould infections are rare; most infections occur in the late post‐transplant period, usually in the context of grade 3–4 GVHD 3,4,25–29 …”
Section: Evidence‐based Recommendations For Antifungal Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…This risk‐adjusted approach has practical implications for clinicians. Most centres, including those in Australia, report that pre‐engraftment, invasive mould infections are rare; most infections occur in the late post‐transplant period, usually in the context of grade 3–4 GVHD 3,4,25–29 …”
Section: Evidence‐based Recommendations For Antifungal Prophylaxismentioning
confidence: 99%
“…Most centres, including those in Australia, report that pre-engraftment, invasive mould infections are rare; most infections occur in the late post-transplant period, usually in the context of grade 3-4 GVHD. 3,4,[25][26][27][28][29] Ullmann et al, instituted prophylaxis as soon as GVHD (of grade 2 or greater severity or meeting the criteria for chronic extensive) was diagnosed. 18 This study demonstrated a reduction in IFI in patients receiving posaconazole compared with those receiving fluconazole or itraconazole (level II evidence).…”
Section: Prophylaxis For Hsct: Late After Engraftmentmentioning
confidence: 99%
“…However, the achievement rate of optimal level could be higher than this rate because the previous reports applied a peak level measured 2 h after administration, while a trough level was applied in the present study [23]. There have been only limited data on the bioavailability of oral solution itraconazole after HSCT, particularly allogeneic HSCT [26,27]. Despite an interindividual variability, our results suggest that oral solution itraconazole (200 mg/day) could be useful in the prophylaxis or treatment of IFD after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 65%
“…4 Itraconazole, a second-generation azole antifungal that is available in intravenous formulations and in a more bioavailable oral solution, is used to prevent fungal infections in HSCT recipients. [5][6][7] Its interactions with calcineurin inhibitors are well documented in the renal allograft setting. [8][9][10] In patients with HSCT, itraconazole has been found to interact with high-dose chemotherapeutic agents, leading to a survival disadvantage owing to enhanced myeloablative chemotherapy-induced organ toxicity.…”
Section: (Pharmacotherapy 2006;26(2):289-295)mentioning
confidence: 99%